Pengembangan LKPD Berorientasi Guided Discovery Learning dengan Internet Assisted Learning untuk Melatihkan Keterampilan Berpikir Kritis - Farhati Zakiyah; Bertha Yonata (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2021)
This study aims to describe the feasibility of a guided discovery learning oriented Student Worksheet to train critical thinking skills on reaction rate materials. The feasibility of this student worksheet is reviewed from three aspects those are validity, practicality, and effectiveness. The research method used was Research & Development (R&D) which was tested on 10 students of class XI IPA MAA Al-Amiriyyah. The results showed that the student worksheet  was declared worthy in term of the validity aspect with the validity of the content reviewed from the criteria of conformity with the material and basic competencies,those are conformity with the guided discovery learning component, conformity with the critical thinking skills component and the suitability of practicum video with reaction rate factors of 100%, 89%, 83% and 91% respectively, and the validity of the constructs reviewed from the language criteria and presentation respectively obtained results of 90% and 91% respectively. , this percentage decrease is described as very valid. Practicality obtained the results of average observation of student activities by 98.51% and the response of learners on the criteria of content, language and presentation obtained results of 91%, 97% and 89% respectively. All three criteria are described as excellent. Effectiveness based on increased pretest-posttest results of critical thinking skills of learners who obtained a 100% completion percentage with an n-gain score in the range of 0.69-0.88 with medium to high categories